Experimental Study on Liquid Flow and Heat Transfer in Rough Microchannels. (23rd November 2019) - Zhang, Xuan; Zhao, Taocheng; Wu, Suchen; Yao, Feng
Abstract : Although roughness is negligible for laminar flow through tubes in classic fluid mechanics, the surface roughness may play an important role in microscale fluid flow due to the large ratio of surface area to volume. To further verify the influence of rough surfaces on microscale liquid flow and heat transfer, a performance test system of heat transfer and liquid flow was designed and built, and a series of experimental examinations are conducted, in which the microchannel material is stainless steel and the working medium is methanol. The results indicate that the surface roughness plays a significant role in the process of laminar flow and heat transfer in microchannels. In microchannels with roughness characteristics, the Poiseuille number of liquid laminar flow relies not only on the cross section shape of the rough microchannels but also on the Reynolds number of liquid flow. The Poiseuille number of liquid laminar flow in rough microchannels increases with increasing Reynolds number. In addition, the Nusselt number of liquid laminar heat transfer is related not only to the cross section shape of a rough microchannel but also to the Reynolds number of liquid flow, and the Nusselt number increases with increasing Reynolds number.